KOMIK SEBAGAI MEDIA ALIH WAHANA LITERASI BUDAYA CERITA KLASIK RAMAYANA DALAM VISUAL MODERN - Improatul Khasanah; Farah Rahmawati; Sasmita Dwi Febila; Sindi Alfiana; Moh. Fikri Zulfikar (Indonesian language and literature education program Majapahit Islamic University, 2025)
This article discusses the process of transforming the classical epic Ramayana into a modern comic titled Grand Legend Ramayana by Is Yuniarto. This study aims to examine how traditional stories can be transformed into modern comics in the manga version so that they are easily accepted by the modern generation. The approach used is the Reading Literature approach with visual and narrative text analysis in comics. The results of the study show that Is Yuniarto innovates in character design, setting, and story style by combining local cultural elements and popular visual styles. Thus, this transformation process strengthens the function of comics as a medium for cultural literacy while bridging the classical literary heritage and the aesthetic tastes of today's society. So that the Grand Legend Ramayana comic is a form of cultural strategy to preserve and modernize traditional values ??in popular media. Keywords: transformation, Ramayana, comics, cultural literacy